2005
DOI: 10.1088/0963-0252/14/2/s01
|View full text |Cite
|
Sign up to set email alerts
|

molecular ions in helium glow discharges: the effect of bulk electron temperature

Abstract: He + 2 molecular ions may be present in a concentration comparable to that of atomic ions in dc helium glow discharges operated at medium pressures (several tens of millibars). We use hybrid discharge simulations to study in a self-consistent way the creation, transport and loss processes of both atomic and molecular ionic species and the role of molecular ions in the self-sustainment of the discharges. In the pressure range where recombination processes are significant, the temperature of the cold (bulk, trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…For the electron density n e-, the values calculated are 1.8 9 10 11 and 5.6 9 10 11 cm -3 without and with filaments, respectively. These values correspond to a mole fraction of 3.3 9 10 -6 and 1.05 9 10 -5 , respectively, in good agreement with a theoretical estimation [30] and simulations performed in similar processes like microwave discharges [14,48,49] and DC discharges [50,51]. Even if it must be recalled that such comparisons may be handled with care because of different experimental conditions (gas, pressure, plasma power, experimental set up, ...), nevertheless the same order of magnitude is found.…”
Section: Effect Of the Gas Activation Modesupporting
confidence: 87%
“…For the electron density n e-, the values calculated are 1.8 9 10 11 and 5.6 9 10 11 cm -3 without and with filaments, respectively. These values correspond to a mole fraction of 3.3 9 10 -6 and 1.05 9 10 -5 , respectively, in good agreement with a theoretical estimation [30] and simulations performed in similar processes like microwave discharges [14,48,49] and DC discharges [50,51]. Even if it must be recalled that such comparisons may be handled with care because of different experimental conditions (gas, pressure, plasma power, experimental set up, ...), nevertheless the same order of magnitude is found.…”
Section: Effect Of the Gas Activation Modesupporting
confidence: 87%
“…The computations are carried out at the following values of the secondary electron emission coefficients: γ He + = 0.15, γ He + 2 = 0.1, γ N + 2 = 0.05, and γ ph = 0.1, where the last value refers to the VUV resonance photons radiated from the He 2 1 P state. These ion-induced yields of the helium ionic species are somewhat lower than those adopted in [31], for He + we base our choice on the findings of [38,39], and for He + 2 we apply the findings of [40] that their yield is ≈ 60% of the yield of atomic ions. These coefficients are known, of course, to have a large uncertainty related to the properties of the electrode surfaces (see, e.g., [41]).…”
Section: Resultsmentioning
confidence: 99%
“…The mobility coefficient usually has an experimental value, and constant characteristic energy values between kT e = 0.1 and 1 eV have routinely been used [44][45][46][47] to obtain the diffusion coefficient D e , via the relation D e /µ e = ekT e . The effect of the assumed value of the (slow, or bulk) characteristic electron energy kT e has been analysed in [16,48]. It has been shown that some of the calculated discharge characteristics (particle densities and the depth of the potential well formed in the negative glow) depend sensitively on the assumed value of kT e , while some other characteristics (particle fluxes and the voltage-current characteristics of the discharge) are basically independent of this value.…”
Section: Transport Coefficientsmentioning
confidence: 99%